Changing vulnerability in Asia: Contagion and systemic risk - Mardi H. Dungey; Moses Kangogo; V. V. Volkov (Asian Development Bank (ADB), 2019)
This paper investigates the changing network of financial markets between Asian markets and those of the rest of the world during January 2003−December 2017 to capture both the direction and strength of the links between them. Because each market chooses whether to connect with emerging markets as a bridge to the wider network, there are advantages to having access to this bridge for protection during periods of financial stress. Both parties gain by overcoming the information asymmetry between emerging and global markets. We analyze networks for four key periods, capturing networks in financial markets before and after the Asian financial crisis and the global financial crisis. Increased connections during crisis periods are evident, as well as a general deepening of the global network. The evidence on Asian market developments suggests caution is needed on regulations proposing methods to create stable networks, because these may result in reduced opportunities for emerging markets.
Keywords: C21; N25; G01; G15; 330; Asian markets; financial crises; networks